The Efficacy of Tournaments for Non-Routine Team Tasks - Florian Englmaier; Stefan Grimm; Dominik Grothe; David Schindler; Simeon Schudy (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Tournaments are often used to improve performance in innovation contexts. Tournaments provide monetary incentives but also render teams' identity and image concerns salient. We study the effects of tournaments on team performance in a non-routine task and identify the importance of these behavioral aspects. In a field experiment (n>1,700 participants), we vary the salience of team identity, social image concerns, and whether teams face monetary incentives. Increased salience of team identity does not improve performance. Social image motivates the top performers. Additional monetary incentives improve all teams' outcomes without crowding out teams' willingness to explore or perform similar tasks again.
Keywords: C93; D90; J24; J33; M52; 330; team work; tournaments; rankings; incentives; identity; image concerns; innovation; exploration; natural field experiment